2004
DOI: 10.1111/j.1463-1326.2004.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel protein kinase C‐β isoform selective inhibitor JTT‐010 ameliorates both hyper‐ and hypoalgesia in streptozotocin‐ induced diabetic rats

Abstract: These observations suggest that PKC-beta contributes not only to diabetic hyperalgesia, but also to hypoalgesia and also contributes to defects in NCV. PKC-beta inhibitor, JTT-010, may be beneficial in suppressing the development of diabetic nerve dysfunction, including hyperalgesia and hypoalgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Ro-32-0432, PKC a inhibitor, was studied for inhibition of oxidative damages in hyperglycemia and effects of these changes in AGE mediated damage in DN in in vitro as well as in in vivo studies. The study demonstrated that JTT-010 ameliorated the reduction in NCV present in diabetic rats [61]. Menne et al [57,58] reported the protection against the development of albuminuria as well as expression of VEGF in knockout mice with PKC a()/)) despite the presence of renal and glomerular hypertrophy.…”
Section: P K C I N H I B I T O R Smentioning
confidence: 92%
“…Ro-32-0432, PKC a inhibitor, was studied for inhibition of oxidative damages in hyperglycemia and effects of these changes in AGE mediated damage in DN in in vitro as well as in in vivo studies. The study demonstrated that JTT-010 ameliorated the reduction in NCV present in diabetic rats [61]. Menne et al [57,58] reported the protection against the development of albuminuria as well as expression of VEGF in knockout mice with PKC a()/)) despite the presence of renal and glomerular hypertrophy.…”
Section: P K C I N H I B I T O R Smentioning
confidence: 92%
“…Here, we use 10 inhibitors collected from the literature, for which half-maximal inhibition constants (IC 50 ) values toward PKC isoforms were determined experimentally: corallidictyal 74, GF-109203X 75, Gö-6976 76, JTT-010 77, K252a 78, midostaurin 79, rottlerin 80, ruboxistaurin 81, staurosporine 82 and UCN-01 83. A simple three-state classification model was constructed; for each PKC isoenzyme, the inhibitors were divided into three classes based on the IC 50 values: class I, good binders (IC 50 < 100 nM), class II, weak binders (100nM < IC 50 < 1 μM) and class III, non-binders (IC 50 > 1 μM).…”
Section: Methodsmentioning
confidence: 99%
“…are widely employed as rat models of type 2 diabetes mellitus in order to analyze the onset of the disease and to develop antidiabetic agents. In contrast, experimental models treated by alloxan or streptozotocin to induce specific damage to pancreatic b cells are widely used as models of diabetic complications [21]. With these experimental models, though, a direct drug effect on the rat cannot be ruled out and a new spontaneous diabetic rat model is currently desired to analyze diabetic complications.…”
Section: Introductionmentioning
confidence: 99%